Polymerase chain reaction-restriction fragment length polymorphism analysis of Helicobacter pylori isolates from patients with gastrointestinal complaints in Eastern Turkey - Ozbey, Gokben; Bahcecioglu, Ibrahim Halil; Ceribasi, Songul; Muz, Adile (Academic Journals, 2012)
The aim of this study was to investigate the genetic variations among isolates of Helicobacter pylori (H. pylori) obtained from patients with gastritis (G) and peptic ulcer (PU) in Elazig Province, East of Turkey and to determine association between restriction fragment length polymorphism (RFLP) types and clinical/histopathological outcomes. Determining the dominant genotypes among H. pylori isolates would detect potential risk and aid in the development of improved treatment and control strategies. Sixty one H. pylori-isolates [29 males and 32 females, 51 with G, 10 with PU (duodenal ulcer (DU) or gastric ulcer (GU)] were examined by polymerase chain reaction-restriction fragment length polymorphism analysis (PCR-RFLP) for detecting the genetic diversity among H. pylori isolates. By (PCR-RFLP) analysis, H. pylori isolates yielded five (A-E) different band profiles. The most common type of H. pylori isolates from patients with chronic active, chronic active non-atrophic and chronic atrophic G was type B (55, 88.9 and 100%, respectively). However, most of the isolates from patients with DU and GU were type D (75 and 100%, respectively). To the best of our knowledge, this is the first report on PCR-RFLP analysis of H. pylori isolates in Elazig Province, the East of Turkey. This study indicated that the genetic heterogenecity among H. pylori isolated from patients is low, and the clinical/histopathological outcomes of H. pylori isolates associated to the RFLP types.
Keywords: Helicobacter pylori; patients; genetic variation; polymerase chain reaction-restriction fragment length polymorphism